Balancing Synchronous and Asynchronous Learning in Indonesian Higher Education: The Role of Reflection in Enhancing Engagement and Outcomes - Dwiniasih, Dwiniasih; Herawan, Endang; Linda, Linda; Aisyah, Siti; Ahmad Chowdhury, Takad (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2026)
Objective: This study investigates the effectiveness of synchronous and asynchronous learning modalities and examines the mediating role of reflection on learning outcomes in fully online Indonesian higher education. Methods: Using a mixed-methods case study approach, data were collected through questionnaires (28 statements) and semi-structured interviews from 20 third-year students at a university in Cirebon, Indonesia. Participants were purposively selected based on completion of technology literacy courses and one semester of experience with both learning modalities. Qualitative data from one lecturer supplemented student perspectives. Data analysis followed the Miles, Huberman, and Saldana model. Results: Asynchronous learning demonstrated high effectiveness in fostering critical thinking (77%), self-paced learning (85%), and draft revision opportunities (88%). Synchronous learning showed strong preference for immediate feedback (71%) but faced significant technical challenges, with 90% reporting audio problems and 65% experiencing delayed engagement. High neutrality in perceived skill improvement indicated uncertainty about comparative effectiveness. Interviews revealed 60% preferred synchronous learning despite technical obstacles, while 40% preferred asynchronous learning for flexibility. Novelty: This study introduces a dual reflection pathway framework explaining how learning modalities activate distinct cognitive processes. Asynchronous learning operates through deliberate reflection via a three-stage mechanism (generalization, monitoring, refinement) with documented iterative cycles, while synchronous learning facilitates spontaneous reflection through immediate social presence. This framework advances theoretical understanding of reflection's mediating role in online learning effectiveness within the Indonesian context.